High Tap Density Spherical Li[Ni0.5Mn0.3Co0.2]O2 Cathode Material Synthesized via Continuous Hydroxide Coprecipitation Method for Advanced Lithium-Ion Batteries. (22nd March 2012) - Yang, Shunyi; Wang, Xianyou; Yang, Xiukang; Liu, Ziling; Wei, Qiliang; Shu, Hongbo
Abstract : Spherical [ Ni 0.5 Mn 0.3 Co 0.2 ] ( OH ) 2 precursor with narrow size distribution and high tap density has been successfully synthesized by a continuous hydroxide coprecipitation, and Li [ Ni 0.5 Mn 0.3 Co 0.2 ] O 2 is then prepared by mixing the precursor with 6% excess Li 2 CO 3 followed by calcinations. The tap density of the obtained Li [ Ni 0.5 Mn 0.3 Co 0.2 ] O 2 powder is as high as 2.61 g cm − 3 . The powders are characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscope (SEM), particle size distribution (PSD), and charge/discharge cycling. The XRD studies show that the prepared Li [ Ni 0.5 Mn 0.3 Co 0.2 ] O 2 has a well-ordered layered structure without any impurity phases. Good packing properties of spherical secondary particles (about 12 μm) consisted of a large number of tiny-thin plate-shape primary particles (less than 1 μm), which can be identified from the SEM observations. In the voltage range of 3.0–4.3 V and 2.5–4.6 V, Li [ Ni 0.5 Mn 0.3 Co 0.2 ] O 2 delivers the initial discharge capacity of approximately 175 and 214 mAh g −1 at a current density of 32 mA g −1, and the capacity retention after 50 cycles reaches 98.8% and 90.2%, respectively. Besides, it displays good high-temperature characteristics and excellent rate capability.